Really learn 100 phrasal verbs (Oxford,New York, 2007)
A teach-yourself workbook to help learners gain a thorough understanding of the meaning and grammar of 100 essential phrasal verbs through guided practice and examples. Each page focuses on one verb and every page follows the same format for ease of use. Verbs are organized by particle so learners can see patterns and the phrasal verbs seem more logical. A "Build Your Vocabulary" section gives information about related nouns and adjectives, synonyms and opposites, and other important meanings of the verb, and recycling and revision pages build confidence. There is also an answer key for reference or revision.
Keywords: Tiếng anh,Tiếng anh,English language,English language; Cụm động từ,Bài tập, các vấn đề,Tài liệu cho người học ngoại ngữ,Verb phrase,Problems, exercises, etc.,Textbooks for foreign speakers